Effect of harvesting site on mineral concentration of browse species found in semi-arid areas of South Africa - K.E. Ravhuhali; H.S. Mudau; H.K. Mokoboki; B. Moyo; L.E. Motsei (Journal of the Saudi Society of Agricultural Sciences, 2023)
The objective of this study was to investigate the effect of the harvesting site on the mineral concentration of selected browse species found in semi-arid areas of South Africa (North West and Limpopo province sites). Five trees from each of the 52 woody browse species were randomly identified and harvested in the North West and Limpopo provinces, South Africa, dried and ground for laboratory analysis. One-way ANOVA was used to analyse the mineral composition of browse species that were not common in both harvesting sites, while a two-way factorial design within a completely randomized experimental design was used to analyse the mineral composition of browse species that were common in both harvesting sites. MANOVA tests were also used in order to assess the species and harvesting site effects on mineral concentrations of species common in both sites. Through ANOVA and MANOVA, there were significant species, harvesting site, and species × harvesting stage effects on all the measured parameters (both macro and micro mineral elements). Phosphorus and calcium concentrations were the highest in Adansonia digitata species, whereas the lowest was obtained in Androstachys jonhsonii browse species in the Limpopo harvesting site. Within each province, Schinus molle found in the North West site had the highest phosphorus, potassium and sodium values when compared to all species within the same province. Vachellia nilotica subsp. kraussiana, M. azedarach and Ziziphus mucronata found in Limpopo province had the highest level of magnesium when compared to other species found within the same province. Senegalia caffra, Grewia flava, Vachellia karroo, Vachellia nilotica subsp. kraussiana, Searsia leptodictya and Melia azedarach found in the Limpopo province had the highest phosphorus level when compared to the same species found in the North West province. Senegalia caffra, Peltophorum africanum, Grewia flava, Vachellia hebeclada and Terminalia sericea found in the North West province had the highest iron levels when compared to the same species found in Limpopo province. There is a need to provide supplementation to those animals exposed to species that have a lower concentration of certain elements.